Enhancing endurance performance predictions: the role of movement velocity in metabolic simulations demonstrated by cycling cadence - Dunst, A. K.; Hesse, C.; Ueberschär, O. (European Journal of Applied Physiology, 2025)
Background Mader`s mathematical model, widely employed for endurance performance prediction, aims to accurately represent metabolic response to exercise. However, it traditionally overlooks dynamic changes in metabolic processes at varying movement velocities.